2010
DOI: 10.1177/229255031001800401
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Autologous Microfat Grafting in Lip Reconstruction of a Whistle Deformity Following Cancer Treatment

Abstract: A whistle deformity is defined as a deficiency in the vertical length of the lip so that the free margins of the upper and lower lips do not meet normally, giving the appearance of whistling. This is a common secondary deformity of the vermilion in patients with cleft lip. A case involving a 61-year-old man who developed a whistle deformity as a result of two wedge resections and postoperative radiotherapy for treatment of squamous cell carcinoma of the lower lip is presented. Hyaluronic acid-based tissue fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Major complications, including blindness or impending necrosis, have been reported following the injection of both HA and autologous fat, but the absence of an antidote as hyaluronidase makes vascular complications more "thoughtful" for lipofilling than HA injection. In reconstructive surgery, it was demonstrated that fat transplantation is a viable option for correcting a post-oncological surgery deformity, even if surgery potentially reduces graft viability secondary to decreased vascularity of the recipient site [79].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major complications, including blindness or impending necrosis, have been reported following the injection of both HA and autologous fat, but the absence of an antidote as hyaluronidase makes vascular complications more "thoughtful" for lipofilling than HA injection. In reconstructive surgery, it was demonstrated that fat transplantation is a viable option for correcting a post-oncological surgery deformity, even if surgery potentially reduces graft viability secondary to decreased vascularity of the recipient site [79].…”
Section: Discussionmentioning
confidence: 99%
“…Schweiger et al [108] reported the use of HA fillers for lip asymmetry correction in cleft lip surgery sequelae. Belyea et al [79] described the use of HA filler combined with autologous microfat for the management of lip whistle deformity secondary to surgical wedge resections and postoperative radiotherapy in squamous cell carcinoma treatment. Stolic et al [109] restored with HA injections a lip notch defect after cleft surgery.…”
Section: Discussionmentioning
confidence: 99%
“…18 For mild deformities dermal fillers or autologous microfat grafting may be an option. 19 More serious deformities need musculo-cutaneous flaps for repair.…”
Section: Discussionmentioning
confidence: 99%
“…However, several sessions are necessary due to the expected resorption (Belyea et al, 2010). In some cases, therefore, a dermis-fat graft can be considered as a differential therapy.…”
Section: Accepted Manuscriptmentioning
confidence: 99%